Push and Pull Driven Development: A Proposed Development Paradigm for West Papua, Indonesia - Marlon Arthur Huwae (Masyarakat Indonesia, 2019)
West Papua is the eastern part of Indonesia with a long history of governance and development scheme under the Dutch and the government of Indonesia. The notion of the state inbetweeness and the state of belatedness is obvious in the development and policy given by the Dutch and the government of Indonesia. The state of inbetweeness is the preference of West Papuan to be either an independent West Papua, Melanesian which is culminated in the Dutch era or an integral part of Indonesia which is constructed under the government of Indonesia. The notion of state belatedness is related to the implementation of a catch-up development model and policy namely special autonomy and partition under Indonesia and the accelerated decolonized development model under the Dutch. It is then important to formulate a proposed development model and paradigm called push and pull driven development to better develop West Papua.